Lithium lines in spectra of C-giants - Yakovina, L.A.; Pavlenko, Ya.V. (Кинематика и физика небесных тел, 2005)
The resonance λ 670.8 nm and subordinate λλ 812.6, 610.4, 497.2, and 460.3 nm lithium lines are investigated as the lithium abundance indicators in spectra of cool C-giants.